Publicity and Transparency. (October 2020) - Wood, Tim; Aronczyk, Melissa
Publicity and transparency are two foundational ideas about the proper structure of democratic communication. In a context of utterly transformed public discourse, it is time to rethink the value of these concepts and especially their relationship to one another. This special issue aims to test prevailing assumptions about these terms as they are reshaped in the present era of organized promotional culture. To begin, the present introduction recasts the concepts of publicity and transparency as tools for analyzing and organizing communicative power rather than as normative ideals in their own right. To this end, we present three core arguments for rethinking transparency and publicity today. First, all acts of transparency entail a redistribution of communicative power but not an inherently egalitarian or democratic one. Second, publicity is the central means by which transparency distributes communicative power. And third, scholars must analyze transparency, like publicity, as a professionalized and industrialized field. By centering questions of power and practice, this special issue aims to animate a research agenda attentive to the relational character of both transparency and publicity in hopes of foregrounding the ways the concepts might be used in service of more equitable political alignments.